Development and clinical validation of a microfluidic-based platform for CTC enrichment and downstream molecular analysis - Cai, Songhua; Deng, Youjun; Wang, Zhe; Zhu, Junyu; Huang, Chujian; Du, Longde; Wang, Chunguang; Yu, Xiangyang; Liu, Wenyi; Yang, Chenglin; Wang, Zhe; Wang, Lixu; et al. (Frontiers in Oncology, 2023)
Background Although many CTC isolation and detection methods can provide information on cancer cell counts, downstream gene and protein analysis remain incomplete. Therefore, it is crucial to develop a technology that can provide comprehensive information on both the number and profile of CTC. Methods In this study, we developed a novel microfluidics-based CTC separation and enrichment platform that provided detailed information about CTC. Results This platform exhibits exceptional functionality, achieving high rates of CTC recovery (87.1%) and purification (∼4 log depletion of WBCs), as well as accurate detection (95.10%), providing intact and viable CTCs for downstream analysis. This platform enables successful separation and enrichment of CTCs from a 4 mL whole-blood sample within 15 minutes. Additionally, CTC subtypes, selected protein expression levels on the CTC surface, and target mutations in selected genes can be directly analyzed for clinical utility using immunofluorescence and real-time polymerase chain reaction, and the detected PD-L1 expression in CTCs is consistent with immunohistochemical assay results. Conclusion The microfluidic-based CTC enrichment platform and downstream molecular analysis together provide a possible alternative to tissue biopsy for precision cancer management, especially for patients whose tissue biopsies are unavailable.